KAJIAN YURIDIS TERHADAP TINDAK PIDANA KORUPSI PROYEK JEMBATAN TORATE CS (Studi Kasus Putusan Nomor 20/Pid.Sus-TPK/PT PAL dan Putusan Nomor 44/Pid.Sus-TPK/2021/PN PAL) - syahrul (JURNAL ILMU HUKUM TOPOSANTARO, 2024)
Author’s conclusion: The judge’s consideration in determining the elements of guilt of the defendant in the corruption of the Torete Bridge construction project, CS, was based on the facts revealed at the trial through the statements of witnesses, expert statements, documentary evidence, indicative evidence and the statements of the defendants in accordance with those relied on in Article 183 Criminal Procedure Code. Even though the application of criminal sanctions against corruption defendants in the Torete Bridge project, CS, is different, it can have a deterrent effect. The application of these criminal sanctions is lower than the demands of the Public Prosecutor. At the appeal level, the judge increased the criminal sanctions and compensation money. Another note, revealed the fact that the defendants Sherly Assa and Christian Andi Pellang are husband and wife. This means that potential opportunities for corruption within the scope of kinship are much more vulnerable than if they did not have a relationship. The dominant intervention of corruption perpetrators who interact with each other because they have family ties has the potential to commit legal violations in the form of Corruption, Collusion and Nepotism. Kesimpulan penulis: Pertimbangan hakim dalam menentukan unsur kesalahan terdakwa korupsi proyek pembangunan Jembatan Torete cs adalah berdasarkan fakta-fakta yang terungkap di persidangan melalui keterangan saksi-saksi, keterangan ahli, alat bukti surat, alat bukti petunjuk serta keterangan para terdakwa bersesuaian yang disandarkan pada Pasal 183 KUHAP. Penerapan sanksi pidana terhadap terdakwa korupsi proyek Jembatan Torete cs sekalipun berbeda tetapi sudah dapat memberi efek jera. Penerapan sanksi pidana tersebut, lebih rendah dari tuntutan Penuntut Umum. Pada tingkat banding, hakim memperberat sanksi pidana dan uang pengganti. Catatan lain, terungkap fakta bahwa terdakwa Sherly Assa dan Christian Andi Pellang adalah suami istri. Artinya, potensi peluang korupsi dalam lingkup kekerabatan jauh lebih rentan dibanding dengan jika tidak memiliki hubungan. Intervensi dominan para pelaku korupsi yang saling berinteraksi karena mempunyai ikatan kekeluargaan sangat berpotensi melakukan pelanggaran hukum dalam bentuk Korupsi, Kolusi dan Nepotisme.